Braided Rivers 2006
DOI: 10.1002/9781444304374.ch3
|View full text |Cite
|
Sign up to set email alerts
|

A Sedimentological Model to Characterize Braided River Deposits for Hydrogeological Applications

Abstract: Braided river deposits form important aquifers in many parts of the world, and their heterogeneity strongly influences groundwater flow and mass transport processes. To accurately characterize these coarse gravelly aquifers, it is important to understand the erosional and depositional processes that form these sediments. Moreover, it is important to evaluate the relative importance of various parameters that determine the preservation potential of different depositional elements over geological time scales. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 97 publications
2
52
0
Order By: Relevance
“…Field observations of gravel pit exposures of Pleistocene coarse deposits in Switzerland showed that the main types of depositional elements are horizontal layers and ''cross-bedded sets [...] with trough-shaped, erosional concave upward lower bounding surfaces'' (Huggenberger and Regli, 2006). The horizontal layers correspond to poorly sorted gravel (the grey gravel (GG) in Table 1).…”
Section: Object and Process Based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field observations of gravel pit exposures of Pleistocene coarse deposits in Switzerland showed that the main types of depositional elements are horizontal layers and ''cross-bedded sets [...] with trough-shaped, erosional concave upward lower bounding surfaces'' (Huggenberger and Regli, 2006). The horizontal layers correspond to poorly sorted gravel (the grey gravel (GG) in Table 1).…”
Section: Object and Process Based Modelsmentioning
confidence: 99%
“…Therefore, they were identified as being formed by scour-pool fills (e.g. Siegenthaler and Huggenberger, 1993;Jussel et al, 1994;Klingbeil et al, 1999;Heinz et al, 2003;Huggenberger and Regli, 2006;Bayer et al, 2011). The trough-fill mostly consists of open ag framework -bimodal gravel couplet cross-beds (OW/BM in Table 1, see also Siegenthaler and Huggenberger, 1993;Huggenberger and Regli, 2006).…”
Section: Object and Process Based Modelsmentioning
confidence: 99%
“…Jussel et al, 1994a;Anderson et al, 1999;Lunt et al, 2004) and make up many groundwater reservoirs worldwide (Huggenberger and Aigner, 1999;Klingbeil et al, 1999;Bayer et al, 2011) and more than two-thirds of the exploited aquifers in Switzerland (Huggenberger, 1993). In this study the sedimentary heterogeneity is characterised following the hierarchy proposed by Huggenberger and Regli (2006). In order of increasing size, this hierarchy consists of sedimentary textures, sedimentary structures, and depositional elements.…”
Section: Introductionmentioning
confidence: 99%
“…1, coarse, braided river deposits are composed of two main depositional elements, remnants of gravel sheets (Huber and Huggenberger, 2015) and trough fills with clear-cut erosional lower-bounding surfaces (e.g. Siegenthaler and Huggenberger, 1993;Jussel et al, 1994a;Beres et al, 1995Beres et al, , 1999Rauber et al, 1998;Stauffer and Rauber, 1998;Teutsch et al, 1998;Anderson et al, 1999;Klingbeil et al, 1999;Whittaker and Teutsch, 1999;Huggenberger and Regli, 2006;Bayer et al, 2011). The sedimentary structure of the remnants of gravel sheets consists of horizontal to sub-horizontal layers with a poorly sorted gravel texture.…”
Section: Introductionmentioning
confidence: 99%
“…Braided rivers are composed of multiple channels that intersect successively, producing braid patterns [Leopold et al, 1957;Howard et al, 1970]. The sediments transported and deposited by these active systems are mainly sand and gravel [Williams and Rust, 1969;Miall, 1977;Siegenthaler and Huggenberger, 1993;Huggenberger and Regli, 2006]. Some finer grain size sediments such as silt or clay may be observed at the surface of an active system after flow recession or vegetation retention, but are generally not as well preserved in the recorded deposits [Huber and Huggenberger, 2015a] due to the high energy of such systems [van derbed-load transport studies [Ashmore, 1988;Dawson, 1988;Surian, 2002] and a wide variety of flume experiments [Ashmore, 1982;Kleinhans and Brinke, 2001;Van De Lageweg et al, 2013].…”
Section: Introductionmentioning
confidence: 99%